Nilai Pendidikan Karakter dalam Teks Meong Palo Karellae - Adly Anugerah (INSIGHT: Indonesian Journal Social Studies and Humanities, 2022)
Abstract. This study aims to describe the form of character education values in the Meong Palo Karallae text. This research is a qualitative research. The data of this study are written data contained in the Meong Palo Karellae text. and documentation. The techniques used to analyze the data are: identification, classification, analysis and description of the data. The results of this study found that in the Meong Pallo Karellae text about the value of character education in the Meong Palo Karellae text, namely the value of divine education, the value of moral education has four parts, namely giving advice, humility, wisdom, character, and the value of social education. , sharing, friendship, kinship, and the value of cultural education including pemmali.Keywords: Value of Character Education, and Text of Meow Palo Karellae.